Examining the Relative Impact of Professional Profile Images and Facial Expressions in Small Business-to-Business Marketing Online. Issue 1 (8th April 2019) - Pawar, Sanchit; Fagerstrøm, Asle; Dimude, Ifeoma Angelica Z; Sigurdsson, Valdimar; Eriksson, Niklas
Abstract: : This article responds to a call for research on the context-specific effects of human images in different online contexts. This study investigates how inherent facial expressions in a consultant's profile image influence the likelihood to contact tendency of small business-to-business website visitors. The results from a conjoint study ( n = 67) demonstrate that a consultant's profile image with a smiling facial expression induced a higher likelihood to contact tendency. While the absence of a profile image reduced this tendency, relatively more than an image with a neutral facial expression. In light of these results, implications for small businesses as well as suggestions for future research are discussed. RESEARCH HIGHLIGHTS: Facial expressions in a consultant's profile image influence customers in online B2B contexts. Facial expressions were the most important stimuli that encourage initial contact from customers. Smiling facial expressions had a positive impact on the likelihood to contact tendency. Absence of a profile image reduced the likelihood to contact. Human facial expressions can be used as a design element to positively influence visitors.